Development of Conflict Resolution Training Using the WhatsApp Application to Improve the Conflict Management Skills of Youth Organization - Indrayati, Ani Sri; Ansori, Ansori; Widiastuti, Novi (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
This study aims to develop a conflict resolution training model assisted by the WhatsApp application to improve the conflict management skills of Karang Taruna members in Majalengka Regency. The method used is Research and Development (R&D) adapted from Borg & Gall with eight stages and involving 42 Karang Taruna members but effectiveness was tested on 20 participants during the final trial stage. Data were collected through interviews, expert validation, practicality questionnaires, and pre-test and post-test tests, then analyzed qualitatively descriptively and quantitatively using paired sample t-test assisted by SPSS. The results showed that the model was declared valid (categorized as feasible), practical based on the improvement of all indicators in limited and broad trials, and effective with a significant increase in pre-test to post-test scores (p < 0.05) and a medium N-Gain category (0.50). This improvement was influenced by the structured training design, the use of contextual case studies, reflective discussions based on WhatsApp groups, and flexible access that allowed for active and repeated participation. Participant responses ranged from good to excellent. The novelty of the study lies in the integration of WhatsApp as a systematic conflict resolution training medium within youth organizations. These findings confirm that WhatsApp has the potential to be an adaptive training medium for improving community-based conflict management competencies.